Macroglossia: An Uncommon Manifestation of Primary Hypothyroidism due to Hashimoto's Thyroiditis in a Teenage Child - Gutch, Manish; Bhattacharjee, Annesh; Sukriti, Kumar; Gupta, Arpit; Somendra Singh, Rao (Journal of the ASEAN Federation of Endocrine Societies, 2017)
Thyroid disorders are prevalent in the paediatric population and untreated hypothyroidism leads to several adverse consequences like mental retardation, neurological impairment, short stature, delayed puberty and increased morbidity. Owing to a wide range of non-specific clinical manifestations, one must have a high index of suspicion for timely diagnosis and treatment of primary hypothyroidism. We describe the case of an adolescent girl who presented with short stature, delayed puberty and feeding difficulties owing to undiagnosed and subsequently untreated hypothyroidism.